Characterization of a novel thermophilic cyanobacterium within Trichocoleusaceae, Trichothermofontia sichuanensis gen. et sp. nov., and its CO2-concentrating mechanism - Tang, Jie; Zhou, Huizhen; Jiang, Ying; Yao, Dan; Waleron, Krzysztof F.; Du, Lian-Ming; Daroch, Maurycy (Frontiers in Microbiology, 2023)
Thermophiles from extreme thermal environments have shown tremendous potential regarding ecological and biotechnological applications. Nevertheless, thermophilic cyanobacteria remain largely untapped and are rarely characterized. Herein, a polyphasic approach was used to characterize a thermophilic strain, PKUAC-SCTB231 (hereafter B231), isolated from a hot spring (pH 6.62, 55.5oC) in Zhonggu village, China. The analyses of 16S rRNA phylogeny, secondary structures of 16S-23S ITS and morphology strongly supported strain B231 as a novel genus within Trichocoleusaceae. Phylogenomic inference and three genome-based indices further verified the genus delineation. Based on the botanical code, the isolate is herein delineated as Trichothermofontia sichuanensis gen. et sp. nov., a genus closely related to a validly described genus Trichocoleus. In addition, our results suggest that Pinocchia currently classified to belong to the family Leptolyngbyaceae may require revision and assignment to the family Trichocoleusaceae. Furthermore, the complete genome of Trichothermofontia B231 facilitated the elucidation of the genetic basis regarding genes related to its carbon-concentrating mechanism (CCM). The strain belongs to β-cyanobacteria according to its β-carboxysome shell protein and 1B form of Ribulose bisphosphate Carboxylase-Oxygenase (RubisCO). Compared to other thermophilic strains, strain B231contains a relatively low diversity of bicarbonate transporters (only BicA for HCO3− transport) but a higher abundance of different types of carbonic anhydrase (CA), β-CA (ccaA) and γ-CA (ccmM). The BCT1 transporter consistently possessed by freshwater cyanobacteria was absent in strain B231. Similar situation was occasionally observed in freshwater thermal Thermoleptolyngbya and Thermosynechococcus strains. Moreover, strain B231 shows a similar composition of carboxysome shell proteins (ccmK1-4, ccmL, -M, -N, -O and -P) to mesophilic cyanobacteria, the diversity of which was higher than many thermophilic strains lacking at least one of the four ccmK genes. The genomic distribution of CCM-related genes suggests that the expression of some components is regulated as an operon and others in an independently controlled satellite locus. The current study also offers fundamental information for future taxogenomics, ecogenomics and geogenomic studies on distribution and significance of thermophilic cyanobacteria in the global ecosystem.